Combined analysis of cecal microbiota and metabolomics reveals the intervention mechanism of Dayuan Yin in acute lung injury - Zhang, Lei; Zhu, Wei; Zhang, Zepeng (Frontiers in Pharmacology, 2024)
The ancient Chinese medicinal formula, Dayuan Yin (DYY), has a long history of use in treating respiratory ailments. and shown to be effective in treating acute infectious diseases. This study aims to explore how DYY may impact intestinal flora and metabolites induced by acute lung injury (ALI).ALI rats were induced with lipopolysaccharide (LPS) to serve as models for assessing the anti -ALI efficacy of DYY through multiple lung injury indices. Changes in intestinal microflora were assessed via 16SrRNA gene sequencing, while cecum contents were analyzed using non-targeted metabonomics. Differential metabolites were identified through data analysis, and correlations between metabolites, microbiota, and in flammatory markers were examined using Pearson correlation analysis. DYY demonstrated a significant improvement in LPS-induced lung injury and altered the composition of intestinal microorganisms, especially reduced the potential harmful bacteria and enriched the beneficial bacteria. At the gate level, DYY exhibited a significant impact on the abundance of Bacteroidota and Firmicutes in ALI rats, as well as on the regulation of genera such as Ruminococcus, Lactobacillus, and Romboutsia. Additionally, cecal metabonomics analysis revealed that DYY effectively modulated the abnormal expression of 12 key metabolic biomarkers in ALI rats, thereby promoting intestinal homeostasis through pathways such as Purine metabolism. Furthermore, Pearson analysis indicated a strong correlation between the dysregulation of intestinal microbiota, differential metabolites, and inflammation.These findings preliminarily Confirm that ALI is closely related to the disorder of cecal microbial and metabolic, and DYY can play a protect ive role by regulating this imbalance, which provides a new understanding of the multi -system linkage mechanism of DYY improving ALI.